2011
DOI: 10.1039/c1jm10155b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of AgI/TiO2 nanocomposite leads to excellent thermochromic reversibility and photostability

Abstract: AgI/TiO 2 nanocomposite was prepared and characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and diffusive reflectance UV-vis (DRUV-vis) absorption spectra at different temperatures. The AgI/TiO 2 nanocomposite exhibits thermochromic switching phenomena at the phase b-a transition temperature of AgI with the evolution of its color from light yellow at ambient temperature to dark khaki at 150 C. It was found for the first time that the formation of the AgI/TiO 2 nanocomposite not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 31 publications
(37 reference statements)
1
46
0
Order By: Relevance
“…This feature can be reasonably assigned to the surface plasmon resonance (SPR) peak of Ag nanoparticles supported on CeO 2 . The SPR peak of Ag nanoparticles red-shifts with their particle size [ 44,45]; therefore, the average size of Ag nanoparticles in Ag/CeO 2 samples follows the order: 3%-Ag/c-CeO 2 > 1%-Ag/c-CeO 2 % 3%-Ag/ r-CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This feature can be reasonably assigned to the surface plasmon resonance (SPR) peak of Ag nanoparticles supported on CeO 2 . The SPR peak of Ag nanoparticles red-shifts with their particle size [ 44,45]; therefore, the average size of Ag nanoparticles in Ag/CeO 2 samples follows the order: 3%-Ag/c-CeO 2 > 1%-Ag/c-CeO 2 % 3%-Ag/ r-CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…tion of orthopositronium atoms formed in large pores [60], s 2 is due to positrons trapped by large size defects [62] located on the surface or subsurface of a sample [63], while the shortest lifetime component (s 1 ) generally arises from the annihilation of free positrons in the bulk section of a material [64]. Thus the relative intensities (I) of s 1 , s 2 , and s 3 provide information about the relative concentration of different defects [65,66].…”
Section: The Longest Lifetime Component (S 3 ) Is Attributed To the Amentioning
confidence: 98%
“…Under ambient condition, it exists in two distinct phases, hexagonal β-AgI and zinc-blende γ-AgI. It has been reported that the presence of a support (e.g.TiO 2 , Al 2 O 3 , SiO 2 ) could stabilize AgI NPs by inhibiting the photographic process [15,19,20]. For example, Hu and co-workers prepared P25-supported AgI by a deposition precipitation route, which exhibited highly efficient and stable photocatalytic activity in destroying bacteria and decomposing K-2G dye [21].…”
Section: Introductionmentioning
confidence: 99%